Estimation of Risk of Recurrence and Toxicity Among Oncologists and Patients With Resected Breast Cancer: A Quantitative Study - Ciria-Suarez, Laura; Jimenez-Fonseca, Paula; Hernández, Raquel; Rogado, Jacobo; Calderon, Caterina (Frontiers in Psychology, 2020)
Shared decision-making regarding adjuvant systemic therapy in breast cancer is based on both properly conveying information about the prognosis of the disease and the benefits and risks of adjuvant treatment. This work proposed to analyze oncologists’ and patients’ perceptions of the risk of recurrence with and without chemotherapy and toxicity, and the factors influencing said impressions. A prospective, cross-sectional, multicenter study involving 281 breast cancer patients and 23 oncologists. Prognosis and Shared Decision Making (SDM) questionnaires were completed by all participants; breast cancer patients also filled out the Brief Symptom Inventory (BSI-18). Oncologists' prediction of risk of relapse without and with chemotherapy (30.4% and 13.3%) and risk of severe toxicity (9.8%) were more optimistic than those of breast cancer patients (78.6%, 29.6%, and 61%, respectively). The greater the severity, the higher the risk of relapse according to the oncologists (p=0.001); not so for the patients. Older physicians and more experienced ones predicted lower risk of relapse with and without chemotherapy and less severe toxicity than younger doctors and those with less experience (p<0.001). Oncologists’ SDM and their prediction of risk of relapsing with chemotherapy correlated negatively with patients’ SDM and their prediction of risk of severe toxicity (p<0.01). These results stress the importance of improving doctor-patient communication in shared decision-making. In breast cancer patients undergoing treatment with curative intent, expectations of being cured would increase and treatment-related anxiety would decrease by enhancing doctor-patient communication to coincide more with respect to risk of relapse and toxicity, thereby enhancing patients’ quality-of-life.